2019
DOI: 10.1080/26395940.2019.1689173
|View full text |Cite
|
Sign up to set email alerts
|

In vitro ingestion and inhalation bioaccessibility of soilborne lead, cadmium, arsenic and chromium near a chemical industrial park for health risk assessment

Abstract: Surface soils were collected near a chemical industrial park in the present study and in vitro inhalation and ingestion bioaccessibility of soilborne lead, cadmium, arsenic and chromium was evaluated using various in vitro bioaccessibility procedures including simulated lung fluid (SLF), artificial lysosomal fluid (ALF), modified Gamble solution (MGS), Solubility/ Bioaccessibility Research Consortium (SBRC) procedure, and in vitro gastrointestinal (IVG) procedure. The in vitro inhalation and ingestion bioacces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Nanjing, which is the core city of China's Yangtze River Delta, is one of the important birthplaces of China's modern chemical industry dating to the 1930s. NJNMHTP, which was formerly known as Nanjing Chemical Industrial Park and established in October 2001, with a total area of 37.10 square kilometers, including the Changlu area of 32.60 square kilometers and the Yudai area of 4.50 square kilometers, is not only a state-level chemical industrial park in which petrochemicals and synthetic materials are developed but is also the second key petrochemical base approved by the Chinese government [35,36]. By 2020, there were 128 enterprises above a designated size in NJNMHTP, including 60 foreign-funded enterprises and more than 20 key enterprises with an annual output value of more than CNY 1 billion.…”
Section: Study Areamentioning
confidence: 99%
“…Nanjing, which is the core city of China's Yangtze River Delta, is one of the important birthplaces of China's modern chemical industry dating to the 1930s. NJNMHTP, which was formerly known as Nanjing Chemical Industrial Park and established in October 2001, with a total area of 37.10 square kilometers, including the Changlu area of 32.60 square kilometers and the Yudai area of 4.50 square kilometers, is not only a state-level chemical industrial park in which petrochemicals and synthetic materials are developed but is also the second key petrochemical base approved by the Chinese government [35,36]. By 2020, there were 128 enterprises above a designated size in NJNMHTP, including 60 foreign-funded enterprises and more than 20 key enterprises with an annual output value of more than CNY 1 billion.…”
Section: Study Areamentioning
confidence: 99%
“…The use of SBFs has been widespread in the literature (Ansoborlo et al 1999;Kokubo and Takadama 2006;Marques et al 2011;Radivojev et al 2019); however, there has been a broad variety of fluids reported and often a lack of commonality, even within recent publications (Hassoun et al 2018;Hu et al 2019;Keller et al 2020;Zhong et al 2020). The study of oral exposure through the GIT has demonstrated the greatest level of harmonisation.…”
Section: Simulated Biological Fluid Specificity To Environmentsmentioning
confidence: 99%
“…In one study an enhanced solubility of Cu, Cr and Mn (PM 1 ) and Pb, Cu and As (PM 2.5 ) in particulate matter was observed in ALF compared to samples exposed to the more neutral Gamble's solution (Wiseman and Zereini 2014). Similarly, ALF gave considerably higher metal releases from vehicle exhaust catalysts (Colombo et al 2008), chromated copper arsenate (CCA)-contaminated soils (Gosselin and Zagury 2020), Pb-containing urban soils (Hu et al 2019;Li et al 2020), as well as increased rare earth element release from indoor air particulate matter (Gao et al 2020), in comparison to Gamble's solution. These results imply that inhaled particles would have to be phagocytised before significant dissolution occurs.…”
Section: Artificial Lysosomal Fluid (Alf)mentioning
confidence: 99%